(untitled) (Sustainability in Debate, 2017)
The problem of the adequate final disposal of municipal solid waste (MSW) is, nowadays, one of the serious environmental challenges. Among several different waste disposal options, sanitary land filling is generally considered the most appropriate. From this perspective, this article aims to analyse the sustainability of a landfill situated at the municipality of Puxinanã, in the Brazilian state of Paraiba. To do so, an index of landfill quality of urban solid waste (IQA) was employed. The index was adapted to match the local conditions. Following collected data, the studied landfill does not meet any existing standards (NBR 8419/1992; 13,896/1997), and exhibits inadequate operating conditions due, among other reasons, to the lack of daily coverage of the waste deposited there. Other negative factors included the lack of separation and sorting of recyclable and compostable waste, and the accumulation of leachate, leading to environmental and human health problems, as well as contributing to the unsustainability of solid waste management.